Evaluation of Parenteral Nutrition Practices at Neonatal Intensive Care Units in Gaza City: Hospital-Based Study - Dalia Ayyad; Jehad El-Hissi; Ihab Almasri (Proceedings, 2023)
Adequate nutritional support for neonates who are sick is challenging due to the difficulty of feeding during their illness and instability. Although feeding through the gastrointestinal tract is the preferred route, there are specific conditions where Parenteral Nutrition (PN) as an adjunctive or sole therapy is necessary. There is a relationship between PN practices and morbidity and mortality in early neonatal life among hospitalized neonates. This study aims to evaluate the short-term impact of Parental Nutrition (PN) practices on the nutritional status of neonates in the two central Neonatal Intensive Care Units (NICUs) in Gaza city. This prospective observational cross-sectional, supported by in-depth interviews, included 50 neonates receiving PN support in two NICUs in Gaza between May 2019 and December 2020. Two data collection questionnaires were adapted from the international Audit Tool. Blood samples were analyzed for pre-albumin as a marker for malnutrition, and SPSS was used to analyze the obtained data. The study highlighted a lack of compliance with national and international guidelines. In 62% of the studied neonates, the daily calories were less than half their recommended energy requirements. There was a significant change in the mean body weight between birth weight and weight after the first and second weeks of PN initiation (p < 0.005). The mortality rate was 16% of the studied neonates. The results showed that neonates who were weaned and discharged home had statistically significantly higher pre-albumin between the 5th and 10th days of PN initiation (p value 0.032) and between the 10th and 15th days of PN initiation (t = 21.894, p value 0.00) compared to neonates who died. This study highlighted the impact of a lack of compliance with national and international standards on the outcome of neonates. There is a need to improve the quality and safety of PN practices at NUS in Gaza City.